2019
DOI: 10.31234/osf.io/u6q4p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How experimental procedures influence estimates of metacognitive ability

Abstract: It is becoming widely appreciated that higher stimulus sensitivity trivially increases estimates of metacognitive sensitivity. Therefore, meaningful comparisons of metacognitive ability across conditions and observers necessitates equating stimulus sensitivity. To achieve this, one common approach is to use a continuous staircase that runs throughout the duration of the experiment under the assumption that this procedure has no influence on the estimated metacognitive ability. Here we critically examine this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…It has been recently shown that the variability in the stimuli presented may lead to inflated estimates of metacognitive performance (Rahnev and Fleming, 2019). To assess whether this was a problem in our data, we ran two separate analyses.…”
Section: Effects Of Experimental Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently shown that the variability in the stimuli presented may lead to inflated estimates of metacognitive performance (Rahnev and Fleming, 2019). To assess whether this was a problem in our data, we ran two separate analyses.…”
Section: Effects Of Experimental Manipulationmentioning
confidence: 99%
“…Another limitation is the use of adaptive staircase procedures throughout the experiment. While maintaining task difficulty constant across trials, conditions, and participants is important to finely estimate metacognitive performance (Rahnev and Fleming, 2019), it also may hinder the relevance of sensorimotor signals as informative cues regarding the difficulty with which a decision was made (Kiani et al, 2014). Thus, a possibility is that sensorimotor signals are more potent cues for confidence estimates under fluctuating task difficulty.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…A recent study (Rahnev & Fleming, 2019) showed that, by exposing observers to different levels of a stimulus, staircase methods produce inflated measures of metacognition when compared to constant stimuli methodologies. As we used separate staircases in our two experimental conditions, if stimulus variability was to be higher in the dual-task condition, this could potentially inflate participants' metacognitive efficiency compared to the single-task condition, thus providing a simple explanation for our result.…”
Section: Stimulus Variabilitymentioning
confidence: 99%
“…Another limitation is the use of adaptive staircase procedures throughout the experiment. While maintaining task difficulty constant across trials, conditions, and participants is important to finely estimate metacognitive performance (Rahnev & Fleming, 2019), it also may hinder the relevance of sensorimotor signals as informative cues regarding the difficulty with which a decision was made (Kiani, Corthell, & Shadlen, 2014). Thus, a possibility is that sensorimotor signals are more potent cues for confidence estimates under fluctuating task difficulty.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%